Quantum chemical hydrogenolysis strategy for elimination of heteroatoms in biomass homologous organic compounds based on oxolane and thiolane - Kanhounnon, G. Wilfried; KOUDJINA, Simplice; KPOTIN, ASSONGBA GASTON; Thomas, Affi Sopi; SAWADOGO, René; Semmeq, Abderrahman; Kosar, Naveem; Badawi, MichaeL; ATOHOUN, YACOLÈ GUY SYLVAIN (My University, 2022)
Bio-oils obtained from biomass contain heteroatoms compounds, like oxolane and thiolane. It is quite difficult for industrialist to purify such refractory bio-oils. One of the efficient strategies for the elimination of heteroatoms is hydrogenolysis process, which results in the formation of H2O and H2S residues as by-products. In this work, quantum chemical studies have been used to analyse the reaction mechanism for the removal of hetero atoms (S and O) as H2O and H2S. We selected B3LYP functional of DFT with Pople's basis set 6-311G(d,p) for computing the hydrogenolysis steps without catalyst. LANL2DZ basis set, is used for studying hydrogenolysis steps involving AlCl3 and as catalysts. All the reactions are analysed at the temperature of 600 K and pressure of 40 bars. Structural, thermodynamic, kinetic properties have been employed to study this process. The analysis of variations parameters during the hydrogenolysis process reveals that these two organic biomass compounds undergo sequential ring opening at C-X (X = O, S) bonds. Butanol and Butanethiol are obtained as a result of first hydrogenolysis process, and these compounds are converted to butane during second catalytic process while eliminating heteroatoms.
Keywords: Quantum chemical hydrogenolysis heteroatoms biomass homologous organic compounds oxolane; thiolane; DFT